Phenol-Rich Botanicals Modulate Oxidative Stress and Epithelial Integrity in Intestinal Epithelial Cells - Andrea Toschi; Andrea Piva; Ester Grilli (Animals, 2022)
Botanicals are mainly known for their role as antimicrobials and anti-inflammatories. Thus, the dual purpose of the study was to verify the antioxidant potential of the tested botanicals and to evaluate their possible modulation of intestinal barrier integrity. As the effects of various phenol-rich extracts were screened, the human Caco-2 cell line was determined to be most suitable for use as the in vitro model for the intestinal epithelium. The tested botanicals, all approved as feed additives, are ginger essential oil, tea tree oil, grape seed extract, green tea extract, olive extract, chestnut extract, pomegranate extract, thyme essential oil, and capsicum oleoresin. The cells were treated with incremental doses of each botanical, followed by measurements of transepithelial electrical resistance (TEER), gene expression of tight junctions (TJs), and reactive oxygen species (ROS). The results showed how different phenol-rich botanicals could modulate barrier functions and oxidative stress in different ways. Interestingly, all the botanicals tested exerted an antioxidant potential by dropping the cytoplasmatic ROS, while the beneficial effect was exerted at different concentrations for each botanical. Our data support the role of plant extracts and essential oils in controlling gut barrier function and in reducing the negative effects of oxidative stress in intestinal epithelial cells, thereby supporting gut barrier functionality.